Construction of Transmission Control System for Digital Signage Services based on Wi-Fi - Soo Kim, Min; Seo, Aria; Chang Kim, Yei (International Journal of Engineering and Technology, 2018)
Background/Objectives: In this paper, we have studied digital signage service operation technology based on Wi-Fi for smart tourism service.Methods/Statistical analysis: We constructed a system based on hybrid positioning technology using GPS, Wi-Fi and Beacon. Then, Wi-Fi transmission control algorithm was developed and applied to the system.Findings: Through the system performance analysis, we obtained the performance evaluation result that the proposed system has low data transmission failure rate and high service utilization rate.Improvements/Applications: We provide service scheduling functions by classifying digital signage service types in real time and non-real time. We have developed a system that enables services withoutinterruption even if a communication failure occurs.Â